1970
DOI: 10.1097/00006254-197004000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Transplacental Passage of Fetal Red Cells in Abortion; Increased Incidence After Curettage and Effect of Oxytocic Drugs

Abstract: Suppression of Lactation-HTLim 1t al.,s, BRrInSH 84 1 1 coer16 uppression of actation-H~akim et al. MEDICAL JOURNAL a thrombus (Wessler and Reimer, 1960). Daniel et al. (1968) suggested that very high levels of plasma factor IX may be related to the development of puerperal venous thrombosis. It would appear reasonable to avoid the use of therapeutic agents which give rise to excessive or prolonged increases in factor IX levels during the puerperiuim. If lactation is to be suppressed with oestrogen it is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
1
0

Year Published

1986
1986
1990
1990

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
2
1
0
Order By: Relevance
“…The risk of FMH after pregnancy termination has been reported in several studies (Katz 1969;Queenan et al 1971;Voigt & Britt 1969). The high frequency of fetomaternal transfusions found in this study corresponds with the data reported by Queenan et al (1971) In pregnancies terminated at 16 and 17 weeks we found a dip in the frequency of FMH as indicated by either a positive Kleihauer test or a raised AFP level.…”
Section: Discussionsupporting
confidence: 92%
“…The risk of FMH after pregnancy termination has been reported in several studies (Katz 1969;Queenan et al 1971;Voigt & Britt 1969). The high frequency of fetomaternal transfusions found in this study corresponds with the data reported by Queenan et al (1971) In pregnancies terminated at 16 and 17 weeks we found a dip in the frequency of FMH as indicated by either a positive Kleihauer test or a raised AFP level.…”
Section: Discussionsupporting
confidence: 92%
“…The present findings confirm earlier ohservations to the effect that fetal blood (or other products) may enter the maternal circulation during elective termination of first-trimester pregnancy (Katz 1969, Quccnan et 01. 1971, Voigt & Britt 1969, Naik et al 1988.…”
Section: Discussionsupporting
confidence: 91%
“…The risein AFP is due to letomaternal haemorrhage: fetal levels of AEP are around a million-fold greater than maternal levels so that transfer ol' very small quantities of fctal blood can produce this phenomenon. Fetomaternal haemorrhage can also occur i n association with elective termination of pregnancy (Katz 1969, Queenan et ul. 1971, Voigt & Britt 1969) is a syntbctic 19-norsteroid which binds to the pi-ogesterone reccptor and therefore acts as an antagonist to the effects of progesterone on target cells (Baulieu 198%.…”
mentioning
confidence: 99%